2011
DOI: 10.1007/s00125-011-2267-5
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and familiality of type 2 diabetes and related quantitative traits in the Botnia Study

Abstract: Aims/hypothesis To study the heritability and familiality of type 2 diabetes and related quantitative traits in families from the Botnia Study in Finland. Methods Heritability estimates for type 2 diabetes adjusted for sex, age and BMI are provided for different age groups of type 2 diabetes and for 34 clinical and metabolic traits in 5,810 individuals from 942 families using a variance component model (SOLAR). In addition, family means of these traits and their distribution across families are calculated. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
162
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(183 citation statements)
references
References 38 publications
(57 reference statements)
7
162
1
2
Order By: Relevance
“…T2DM is a complex disease with various involved factors (Mathias et al, 2009). Previous studies have reported that the preva-lence rates of T2DM vary substantially throughout the world (International Diabetes Federation, 2012), and relatives of T2DM patients are at greater risk for developing the disease than the general population (Newman et al, 1987;Mathias et al, 2009;Almgren et al, 2011). Newman et al found that 58% of monozygotic co-twins of diabetic twins were themselves diabetic compared with an expected prevalence of 10% (Newman et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…T2DM is a complex disease with various involved factors (Mathias et al, 2009). Previous studies have reported that the preva-lence rates of T2DM vary substantially throughout the world (International Diabetes Federation, 2012), and relatives of T2DM patients are at greater risk for developing the disease than the general population (Newman et al, 1987;Mathias et al, 2009;Almgren et al, 2011). Newman et al found that 58% of monozygotic co-twins of diabetic twins were themselves diabetic compared with an expected prevalence of 10% (Newman et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In current study we ascertained that the weakest factors of Cardiovascular morbidity were decreased level of HDL-C and also type 2 diabetes. In the Botnia Study [33] which was a large family study of subjects with type 2 diabetes and their relatives in western Finland, the presence of the metabolic syndrome was associated with a 6-fold increase in CVD mortality during the 6.9-year follow-up [34]. In persons with MetS who do not have diabetes, increased risks of CVD and CHD mortality remain.…”
Section: Discussionmentioning
confidence: 99%
“…Given the inverse correlation between traditional consumption of dietary components increasing GDM risk and current incidence of GDM, high glycemic foods and dairy may have acted as selective agents on metabolism during pregnancy. Since GDM is very likely to have a genetic basis --67% of the risk of type 2 diabetes for adults younger than 60 is heritable [38], and women with GDM have 7--12x elevated risk for type 2 diabetes [39,40] --natural selection can act on its underlying risk factors. Therefore, any population environmentally at risk for GDM without access to C--sections should experience selection against genetic risk factors for GDM.…”
Section: Metabolic Disorders and Selection During Pregnancymentioning
confidence: 99%